Immunotherapy in pancreatic cancer and the importance of tumour testing. Issue 7 (16th July 2020) - Ngo, Phuong; Shanshal, Mohamed; Rojan, Adam
Abstract : Advanced pancreatic cancer carries a poor prognosis and has traditionally been treated with chemotherapy. However, immunotherapy has made great strides in a subset of patients depending on mismatch repair/microsatellite status. We present a patient with locally advanced pancreatic cancer treated with neoadjuvant chemotherapy followed by surgery and additional adjuvant chemotherapy whose disease progressed while on adjuvant chemotherapy. Tumour testing showed a mismatch repair mutation and high microsatellite instability, making her eligible for treatment with immunotherapy. Germline genetic testing confirmed the clinical suspicion of Lynch syndrome. She has had isolated sites of progression treated with radiation but overall has been receiving immunotherapy for more than 3 years, highlighting the importance of tumour testing as it may allow for additional treatment options and improved survival.